Argentina's Private Universities: Stringent Regulation of a Small but Consolidated Sector - Salto, Dante (International Higher Education, 2022)
Significant resistance to private universities in Argentina has resulted in a small, but strong participation of this sector in higher education. Core debates about private actors in education have evolved from vigorous opposition to more nuanced discussion about their fundamental role. However, the more prestigious and larger public sector still enjoys much governmental support in terms of finance and regulations, which has led the private sector to rely mostly on tuition revenue.